THE IMPACT OF BANK DIVERSIFICATION ON STOCK MARKET VALUE: EVIDENCE FROM PAKISTAN (Academicia Globe: Inderscience Research, 2021)
Although commercial banks have gradually followed the diversification strategy and sneaked into non-traditional activities for further income sources, studies on diversification outcomes provide diverse results. This research investigates how stock market values bank diversification using a data set of Pakistani listed banks for the period 2009-2017. Over all we find a negative relationship between bank diversification and stock market valuation. This implies investor prefer to invest in the banks who focus on traditional activities.